2016
DOI: 10.1161/strokeaha.115.011657
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Original and Shortened Versions of the National Institutes of Health Stroke Scale in Ischemic Stroke Patients of Intermediate Severity

Abstract: Analyses were performed using data from the Chinese Medicine Neuroaid Efficacy on Stroke recovery (CHIMES) study, an international, randomized, placebo-controlled, double-blind trial investigating the efficacy of MLC601 on stroke recovery in patients with ischemic stroke of intermediate severity in the preceding 72 hours (clinicaltrials.gov NCT00554723). 10,11 Patients were randomly allocated to either MLC601 or placebo for 3 months as add-on to standard stroke care.Patients were assessed at baseline, day 10 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The NIHSS score [ 4 ] includes language, facial paralysis, consciousness level, and gaze function, with the total score of 45 points; the higher the score indicates the worse the degree of nerve defect.…”
Section: Methodsmentioning
confidence: 99%
“…The NIHSS score [ 4 ] includes language, facial paralysis, consciousness level, and gaze function, with the total score of 45 points; the higher the score indicates the worse the degree of nerve defect.…”
Section: Methodsmentioning
confidence: 99%
“…S1. Age (mean 64.87 ± 0.60 and 95% CI 63.69 -66.05), gender (female : male = 68 : 157), and score of National Institute stroke scale [12,13] (NIHSS) of patients were recorded. Neutrophil count, neutrophil to lymphocyte ratio (NLR) in the peripheral blood and the infarct sizes within 24h after symptom onset were analyzed.…”
Section: Patientsmentioning
confidence: 99%
“…Our analysis performed in a population of patients with AIS of intermediate severity (b-NIHSS [8][9][10][11][12][13][14] shows that long-term functional outcome is specifically associated with the level of their baseline limb motor score of the NI-HSS (b-NIHSS-LMS), in addition to their level of b-NI-HSS. Nested logistic regression analysis showed that b-NI-HSS and b-NIHSS-LMS were independently associated with functional independence (mRS 0-1).…”
Section: Discussionmentioning
confidence: 87%
“…In a previous study comparing the 15-item and shortened versions of the NIHSS, we showed that the original 15-item NIHSS displayed the largest effect size for discriminant ability and responsiveness to change on mRS compared to its shortened versions [14]. On the other hand, to measure the broader disability that can result from stroke in later post-acute stages, it is preferable to use other rating scales measuring functional outcomes which are widely used in RCTs and requested by regulatory bodies [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation